Shopping mall image: systematic review of 40 years of research. Issue 1 (1st January 2017) - Gomes, Renata Maria; Paula, Fabio
Abstract: Scholars have measured mall image, or mall attractiveness, since the mid-1970s. The models proposed are strongly rooted in the retail location and store image theories. However, apart from this common ground, the constructs adopted share few similarities with respect to the selection of mall attributes used to measure mall image. As a result, the extant literature is fragmented, offering several different models that are difficult to compare. This state-of-affairs is averse to the progress of knowledge, as it lacks external validity needed when different contexts are investigated, which is the case of shopping centres established in several different urban environments, countries and cultures. As a result of a systematic literature review, which employed bibliometric analysis and content analysis, both the roots and the frontier of research were identified. A list of mall image attributes was generated and identified those that seemed theoretically more relevant in capturing the construct of mall image.